Increased Cycling Performance of Li-Ion Batteries by Phosphoric Acid Modified LiNi0.5Mn1.5O4 Cathodes in the Presence of LiBOB - Maheeka Yapa Abeywardana; Nina Laszczynski; Matthias Kuenzel; Dominic Bresser; Stefano Passerini; Brett Lucht (International Journal of Electrochemistry)
LiNi0.5Mn1.5O4 (LNMO), which has an operating voltage of 4.8 vs Li/Li+ and a theoretical capacity of 147 mAh g−1, is an interesting cathode material for advanced lithium ion batteries. However, electrolyte decomposition at the electrode can gradually decrease the capacity of the battery. In this study, the surface of the LNMO cathode has been modified with phosphoric acid (PA) to improve the capacity of the LNMO/graphite full cell. Modification of LNMO cathodes by PA is confirmed by surface analysis. Additionally, the presence of lithium bis-(oxalato) borate (LiBOB) as an electrolyte additive further enhances the performance of PA modified LNMO/graphite cells. The improved performance of PA modified cathodes and electrolytes containing LiBOB can be attributed to the suppressed Mn and Ni deposition on the anode. Elemental analysis suggests that the Mn and Ni dissolution is significantly reduced compared to unmodified LNMO/graphite cells with standard electrolyte.